HELP SEEKING ATTITUDES FOR MENTAL ILLNESSES AMONG UNDER-GRADUATE MEDICAL STUDENTS IN LAHORE - Amin, Hafsa; Wazeer, Mahnoor; Imran, Nazish; Rashid, Amna; Kiran, Roop; Haider, Imran Ijaz (Journal of Pakistan Psychiatric Society, 2023)
Objective: The reluctance of medical students to seek help for stress is attributed to a lot of factors involving stigma, their help-seeking attitudes and psychological openness. The objective of this study is to gauge help seeking attitudes for stress and mental health issues among Pakistani medical students. Design: Two questionnaires were used to form a self-administered questionnaire, including Hopkins Symptom Checklist (SCL-5) and Inventory of Attitudes towards Seeking Mental Health Services (IASMHS). Place & duration of study: Students from King Edward Medical University, Lahore and Fatima Memorial Hospital were administered the questionnaire in physical form as well as an online version. Responses were gathered over a time of 3 months. Methods: We conducted a cross-sectional survey in two selected medical colleges in Lahore in 2022. After IRB approval and informed consent, a self-administered questionnaire which included Hopkins Symptom Checklist (SCL-5) and Inventory of Attitudes towards Seeking Mental Health Services (IASMHS) was utilized for data collection. Analysis was conducted with SPSS 26. Results: Six hundred and forty-one undergraduate medical students participated in the study with majority being female (64.2%) and hostellers (59%). SCL- 5 scores of the participants (mean=13.36, S. D=4.95) showed moderate levels of distress among students. Participants’ mean Attitude Score on IASMHS was 53.66 (S. D=10.72). Attitudes towards help seeking were fairly negative especially with regard to feeling indifferent towards stigma (mean=18.95, S.D=5.69). Student’s attitudes reflected some psychological openness (mean=14.48, S.D=5.35), while propensity to seek help was slightly better (mean=20.23, S.D = 4.75). Females and clinical year students showed more positive attitudes towards help seeking as compared to males and students belonging to pre-clinical years (P<0.05). Conclusion: The study showed that stress among under-graduate medical students remains a significant issue. While female students and clinical years’ students portrayed better help seeking attitudes towards mental illnesses and stress, further studies including interventions to address mental illness stigma are required to improve the trend.